Finite Element Modeling Piezoelectric Materials under Thermal Loads with Application for Quantum Dots - Milan Zmindak; Pavol Novak; Peter Bishay (Communications - Scientific letters of the University of Zilina, 2017)
Significant research has been done in the analysis of properties of quantum dots over the previous decade. A 3D finite element model is developed to analyze quantum dots (QD) under static thermal loads. The lattice mismatch between the quantum dot and the piezoelectric matrix is created by different thermal properties of materials at enhanced temperature of this electronic structure. The fully coupled thermo-piezoelectricity is applied to the analysis of the problem. Commercial FEM software ANSYS was used for analysis. Finite element numerical results are given for the dot with a cubic shape. Numerical results for the InAs/GaAs QD nanostructure show that the elastic and electric fields are strongly influenced by the differences between the material properties of the piezoelectric QD and matrix.